Silica-based superhydrophobic coating by a single-step process. Issue 3 (September 2013) - Kousaalya, Adhimoolam Bakthavachalam; Garg, Nitish; Kumar, Ravi
Abstract : Silica-based superhydrophobic coatings were produced on glass substrate by dip-coating process. Colloidal solutions containing nanoparticles of silica synthesized via seed growth method (single- and dual-sized particles) and dispersed in three different solvents, ethanol, silica sol and acidic silica sol, were used. Coatings with dual-sized particles in ethanol showed superhydrophobicity with a water contact angle of 155°. The coating adhesion was improved with the use of acidic silica sol as solvent. Coatings prepared from colloidal solution containing 30 wt.% of dual-sized silica particles of 600 and 800 nm in acidic silica sol, showed hydrophilicity with water contact angle of 45° before heat treatment due to the presence of –OH groups from acidic sol. After heat treatment at 250°C for 2 h in atmospheric ambience, the –OH groups reacted to form cross-linked Si-O-Si resulting in superhydrophobicity of the coating with water contact angle of 147°. In this work, silica based superhydrophobic coating was fabricated by adjusting the ratios of the dual-sized silica particles without carrying out any secondary step such as chemical modification or fluorination process on the coating.